2020
DOI: 10.1029/2020jg005812
|View full text |Cite
|
Sign up to set email alerts
|

Mangroves as a Source of Greenhouse Gases to the Atmosphere and Alkalinity and Dissolved Carbon to the Coastal Ocean: A Case Study From the Everglades National Park, Florida

Abstract: Most research evaluating the potential of mangroves as a sink for atmospheric carbon has focused on carbon burial in sediments. However, the few studies that have quantified lateral exchange of carbon and alkalinity indicate that the dissolved carbon and alkalinity export may be several-fold more important than burial. This study aims to investigate rates and drivers of alkalinity, dissolved carbon, and greenhouse gas fluxes of the mangrove-dominated Shark River estuary located in the Everglades National Park … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 73 publications
4
26
0
Order By: Relevance
“…The slopes imply that the production of DIC and TA can be a result of different biogeochemical reactions, especially at the estuary and shelf scales due to sources other than mangroves. Sulfate reduction seems to represent the main organic carbon mineralization pathway within the mangrove (groundwater and tidal creek samples) as observed in other mangrove systems (Sippo et al 2016;Twilley et al 2019;Reithmaier et al 2020). However, other processes, such as calcium carbonate dissolution, might represent an important source of alkalinity in mangroves and on the shelf (Macreadie et al 2017;Volta et al 2020;Saderne et al 2021).…”
Section: Carbon Speciationmentioning
confidence: 65%
“…The slopes imply that the production of DIC and TA can be a result of different biogeochemical reactions, especially at the estuary and shelf scales due to sources other than mangroves. Sulfate reduction seems to represent the main organic carbon mineralization pathway within the mangrove (groundwater and tidal creek samples) as observed in other mangrove systems (Sippo et al 2016;Twilley et al 2019;Reithmaier et al 2020). However, other processes, such as calcium carbonate dissolution, might represent an important source of alkalinity in mangroves and on the shelf (Macreadie et al 2017;Volta et al 2020;Saderne et al 2021).…”
Section: Carbon Speciationmentioning
confidence: 65%
“…Export values have been retrieved from Reithmaier et al. (2020b) for the Everglades and from Sippo et al. (2016) for the remaining sites.…”
Section: Discussionmentioning
confidence: 99%
“…Reithmaier et al (2020b).b Sippo et al (2016).c Brown et al (2018).d Maher et al (2015).e Reithmaier et al (2020a). f Lee and Patterson (2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…of $ 15-20 Pg C on global area basis; Donato et al 2011). Lines of evidence have revealed that mangroves can export a significant amount of dissolved organic and inorganic carbon (DOC, DIC) and particulate organic carbon (POC) to the sea (Dittmar et al 2006;Ray et al 2020;Reithmaier et al 2020). Mangrove pore water-derived C flux is equivalent to $ 30% of global river inputs (Chen et al 2018).…”
mentioning
confidence: 99%